Depth-electrode stimulation and concurrent functional MRI in humans: Factors influencing heating with body coil transmission - Hiroyuki Oya; Ralph Adolphs; Matthew A. Howard; J. Michael Tyszka (NeuroImage: Clinical)
Electrical-stimulation fMRI (es-fMRI) combines direct stimulation of the brain via implanted electrodes with simultaneous rapid functional magnetic resonance imaging of the evoked response. Widely used to map effective functional connectivity in animal studies, its application to the human brain has been limited due to safety concerns. In particular, the method requires reliable prediction and minimization of local tissue heating close to the electrodes, which will vary with imaging parameters and hardware configurations. Electrode leads for such experiments typically remain connected to stimulators outside the magnet room and cannot therefore be treated as electrically short at the radio frequencies employed for 1.5 T and 3 T fMRI. The potential for significant absorption and scattering of radiofrequency energy from excitation pulses during imaging is therefore a major concern. We report a series of temperature measurements conducted in human brain phantoms at two independent imaging centers to characterize factors effecting RF heating of electrically long leads with body coil transmission at 3 Tesla for temporal RMS RF transmit fields (B1+rms) up to 3.5 µT including multiband echo planar imaging and 3D T2w turbo spin echo imaging. Under all conditions tested, with one exception, the temperature rise measured immediately adjacent to electrode contacts in a head-torso phantom with body coil RF transmission was less than 0.75 °C. We provide detailed quantification across a range of configurations and conclude with specific recommendations for cable routing that will help ensure the safety of es-fMRI in humans and provide essential data to institutional review boards.